Erythritol's Impact on Body Weight and Overall Health - Jagoda Marcinkowska; Marek Miśkiewicz; Jakub Ptak; Rafał Noga; Adrian Herc; Karolina Koczkodon; Victoria Teska; Jakub Perłowski; Marcelina Sawczuk; Mariusz Krompiewski (Nicolaus Copernicus University in Toruń, 2024)
Erythritol, a sugar alcohol derived from carbohydrate hydrolysis, is gaining attention for its unique properties and potential health benefits. While it occurs naturally in small quantities in certain foods, industrial production methods have made it a popular sugar substitute in various consumer products. Erythritol's sweetness coupled with its low or negligible calorie content, positions it as an attractive option for individuals seeking to manage weight or diabetes. Unlike some polyol sweeteners, erythritol's absorption in the small intestine does not lead to gastrointestinal distress, making it widely used in foods and beverages. Research indicates that erythritol's ingestion does not significantly impact serum glucose or insulin levels, making it suitable for individuals with diabetes or those managing carbohydrate intake. Moreover, erythritol shows promise in improving endothelial function and protecting against vascular complications associated with diabetes. Individuals with carbohydrate disorders or those who are overweight represent only a segment of the population that may benefit from erythritol. This sweetener also offers a spectrum of advantageous effects on oral and gastrointestinal health. However, while erythritol offers numerous potential benefits, further studies are needed to fully understand its long-term effects on the human body. This review compiles current data on erythritol's metabolism and underscores erythritol's multifaceted and beneficial potential role in health.